Anticoagulant Medications: A Comparative Review of Aspirin, Warfarin, Heparin, and Apixaban - Hamza Khalifa Ibrahim; Areej Muftah Mohammed; Amal Muftah Abdalaziz; Rahma Alfetury Alside; Huda Muftah Masoud (Information Technology and Science (ITScience), 2024)
Anticoagulant drugs play a role, in preventing and treating blood clotting disorders. This article offers an in depth look at four prescribed anticoagulants; aspirin, warfarin, heparin and apixaban. We delve into how they work, when they are used recommended doses, how they are processed in the body, side effects and the need, for monitoring. Moreover, we compare the effectiveness, safety profiles and practical considerations of each medication to assist healthcare providers in making informed treatment choices. By grasping the features of these anticoagulants medical professionals can enhance treatment outcomes while reducing the chances of bleeding issues.